The Effect Of Stocking Density andKind of Feed On Growth and Survival Rate Of Java Barb Larvae (Barbonymus gonionotus) - Rudi Pratama; Sukendi Sukendi; Hamdan Alawi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractThe aim of this research was to determine the effect of stocking density and kind offeed on growth and survival rate of Java barblarvaereared with a water recirculation system. This research was conducted from November-December 2018 at the Fish Hatchery and Breeding Laboratory, Fisheries and Marine Science Faculty Riau University. The Method used was a Factorial Completely RandomizedDesign with two factors.The first was stocking density with three levels, namely 5 larvae/L (T5), 10 larvae/L (T10) and 20 larvae/L (T20). While the second factor waskind of feed with two levels namelyArtemia nauplii (Pa) and Tubifex warm (Pt).The larvae were reared in 10 L-glass aquariumwith a water recirculating system for 40 days. The result showed that stocking density and kind of feedgave asignificant effect in absolute weight, absolute length, average growth rateand survival rateof java barb larvae. The larvae stocked at density of5 larvae/L and fed onArtemia naupliwere significanthy(P<0,05) the highest inabsolute weight (1,11 gr), absolute length (4,35 cm), spesific growth rate (12,49 %/day)and survival rate (99,33 %). The water quality parameters during research were rangedtemperature25,3-27,8°C, pH 5,1-6,5 and dissolved oxygen 4,1-5,2 mg/l. Keywords : Stocking denstity, Kind of feed,Java barb larvae,Growth and Survival rate